Implementation of data collection for the Italian Arthroplasty Registry. Learning curve of 5 surgical centers - Tarantino, Alessio; Romanini, Emilio; Cioffi, Raffaele; Silleni, Francesca; Valentino, Luigi; Scarnera, Pierpaolo; Fidanza, Andrea; Torre, Marina; Ciminello, Enrico; Logroscino, Giandomenico; Calvisi, Vittorio (Lo Scalpello - Journal, 2022)
Introduction. Arthroplasty registries are widely recognized as an effective tool, providing a constant flow of data that can guide the clinical practice of orthopedic surgeons. Despite their usefulness, their implementation in Italy has historically proved to be laborious. In fact, many surgeons are unwilling to participate, claiming as reason for this inertia the additional work needed in an already overloaded clinical practice. Material and methods. Five operators from five different hospitals without any previous experience with arthroplasty registries entered all the data relevant to the joint replacements performed in their structures in a dedicated online platform and measured the time needed for any input. The learning curve for each operator was then drawn. Results. After the input of 20 procedures, all operators reached a plateau of about 2-3 minutes to record a single intervention. Conclusions. The modest amount of time required to compile registry data sheet should not represent a limitation for surgeons to enter the information into a national registry.